Pengaruh Experiential Marketing Terhadap Loyalitas Konsumen Mobil Ayla Pada PT. Astra International Tbk Daihatsu Cabang Malalayang - Pati, Natalia Johana; Kalangie, John A. F.; Walangitan, Olivia Ch (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
Along with the development of the era, the competition of the business worldish getting tighter. Many competitors with the best quality sprung up the hearts of consumers. Referring up the current conditions then used a form of marketing that trieas to analyzeconsumers by using psychological models in analyzing consumer behaviors experiential marketing. In this approach, the marketer provides the product by touching the senses, the heart, and the mindsof consumers. This will be good for the company because satisfied costumers usually tell their experience using a companyâ€™s productor service to others. The purpose og this research is to find out whether there is an influence Experiential Marketing to Consumer LoyaltyThe result of this study indicate thatthere is a positive influence of calculated larger than the able (2,733>1,933). Based on the result of research data that has been processed, it can be concluded that the influence of Experiental Marketing on consumer loyalty is at a very strong correlation level of 0,687 or 68,7% while 31.3% influenced by other variable not examined in this research.Â Keywords: experiential marketing, consumer loyaltyÂ